Design chart for the modified hyperbolic method - Guo, Wei (2020)
The modified hyperbolic method is used in practice to predict the ultimate primary consolidation settlement of compressible ground. This paper presents a new relationship between the average degree of consolidation for combined vertical and horizontal consolidation Uvh and the non-dimensional vertical time factor Tv, with a new parameter, νhv, introduced. νhv is defined as the ratio of the time factor in the horizontal direction to that in the vertical direction. This relationship is then adopted to calculate the slope of the linear segment of the theoretical hyperbolic plot (Tv/Uvh vs Tv), λ which is a key factor in the modified hyperbolic observational method presented by Tan (1995). A design chart for λ as a function of νhv is proposed. Using this design chart, the determination for λ can be simplified from a procedure involving three parameters to only one, νhv. A new procedure for the use of the modified hyperbolic method is proposed. The new procedure is verified using a well-documented case history.